2014
DOI: 10.1371/journal.pgen.1004759
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Phlebiopsis gigantea Genome, Transcriptome and Secretome Provides Insight into Its Pioneer Colonization Strategies of Wood

Abstract: Collectively classified as white-rot fungi, certain basidiomycetes efficiently degrade the major structural polymers of wood cell walls. A small subset of these Agaricomycetes, exemplified by Phlebiopsis gigantea, is capable of colonizing freshly exposed conifer sapwood despite its high content of extractives, which retards the establishment of other fungal species. The mechanism(s) by which P. gigantea tolerates and metabolizes resinous compounds have not been explored. Here, we report the annotated P. gigant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(97 citation statements)
references
References 92 publications
3
91
3
Order By: Relevance
“…These microorganisms are essential to initiate lignocellulose degradation and complete the carbon cycle [41]. In particular, primary colonizers may need a battery of lipases with different affinities, as these substrates have different composition in lipids and extractives [42]. The presence of versatile lipases in litter-degrading fungi was lower, probably because soil litter has previously been colonized and partially degraded by other microorganisms [43].…”
Section: Discussionmentioning
confidence: 99%
“…These microorganisms are essential to initiate lignocellulose degradation and complete the carbon cycle [41]. In particular, primary colonizers may need a battery of lipases with different affinities, as these substrates have different composition in lipids and extractives [42]. The presence of versatile lipases in litter-degrading fungi was lower, probably because soil litter has previously been colonized and partially degraded by other microorganisms [43].…”
Section: Discussionmentioning
confidence: 99%
“…Biomek FX Automated liquid handling robot (Beckman Coulter) was used to transfer 150 μl buffer to peroxidase Genome sequence published from same species and/or the same strain [12,[30][31][32][33] or available at Joint Genome Institute webpages [30]. Synonym for P. rivulosus is Obba rivulosa T241i.…”
Section: Microplate Assaymentioning
confidence: 99%
“…While exceptions are known (Hori et al 2014), laccases have been found in most white-rot fungi examined (Baldrian 2006), often with several genes within one organism (Kilaru et al 2006). These exoenzymes have adapted to a relatively narrow range of environmental conditions suitable for fungal growth.…”
Section: Introductionmentioning
confidence: 99%